A Metataxonomic Approach Could Be Considered for Cattle Clinical Mastitis Diagnostics - Oultram, Joanne W. H.; Ganda, Erika K.; Boulding, Sarah C.; Bicalho, Rodrigo C.; Oikonomou, Georgios (Frontiers in Veterinary Science, 2017)
Mastitis is one of the most costly diseases affecting the dairy industry and identification of the causative microorganism(s) is essential. Here we report the use of next generation sequencing of bacterial 16s rRNA genes for clinical mastitis diagnosis. We used 65 paired milk samples, collected from the mastitic and a contralateral healthy quarter of mastitic dairy cattle to evaluate the technique as a potential alternative to bacterial culture and targeted PCR. One large commercial dairy farm was used, with one trained veterinarian collecting the milk samples. The 16s rRNA genes were individually amplified and sequenced using the MiSeq platform. The MiSeq Reporter was used in order to analyse the obtained sequences. Cattle were categorised according to whether or not one of the ten most abundant bacterial genera in the mastitic quarter exhibited an increase in relative abundance between the healthy and mastitic quarters equal to, or exceeding, two-fold. We suggest that this increase in relative abundance is indicative of the genus being a causative mastitis pathogen. Well known mastitis-causing pathogens such as Streptococcus uberis and Staphylococcus spp. were identified in most cattle. We were able to diagnose 53 out of the 65 studied cases and identify potential new mastitis pathogens such as Sneathia sanguinegens, and pathogens such as Listeria innocua, which is difficult to identify by bacterial culture because of its fastidious nature.